THE COMMUNICATIVE APPROACH TOWARD STUDENTS SPEAKING ABILITY OF THE SEVENTH GRADE STUDENTS AT SMP NEGERI 1 LICIN BANYUWANGI - Wageyono (MAN Insan Cendekia Jambi, 2020)
Speaking ability in the foreign language teaching is not enough merely to provide students with opportunities to speak in conversation or class discussion. The various approach which can applied by teacher or source of information in the classroom activities to support the students to be for familiar to the target language as the objective of learning. This all intended to modify the students in order to be able to communicative approach. This approach used to help the teacher in interesting the students achievement in order become to communicatively competence. Therefore, this study tried to discover students’ speaking ability in communication for the firs year students of SMP N 1 Licin in the school year 2019/2020. There were two research questions formulated as follow: (1). To what extent is the level of students’ speaking ability in English for beginning level of the first year students’ of SMP N 1 Licin in the school year 2019/2020? (2). To what extent is the effectives of communicative approach toward speaking ability for beginning level of the firs year students of SMP N 1 Licin in the school year 2019/2020? This study was experimental research ; the target population of this study was all the firs year students of SMP N 1 Licin in the school year 2019/2020. The researcher took 50 students as the sample of the study, 24 students as the experimental group and 26 students as the control group. To the collect the data, the researcher used speaking test in oral term which referns to the retelling picture and tape recorder. In analyzing te data, the researcher used the comprehensive description of FSI procedure and the then corversed with the criteria of the weighting table of the comprehensive description of FSI procedure. After collecting and calculating the data, the found that the mean score for the experimental group was 60, and for the control group was 41.5. while, in testing the hypothesis, the writer used t-test formula. The researcher found that t-test was 1.77, and t table in significant rank 5% was 2.02 (1.77<2.02). so, the alternative hypothesis was rejected and the null hypothesis could be accepted. It means that there is no significant effect of communicative approach toward students speaking ability.